IGF1-mediated human embryonic stem cell self-renewal recapitulates the embryonic niche - Sissy E. Wamaitha (Nature Portfolio, 2020)
The signals regulating the establishment and maintenance of the pluripotent epiblast in human embryos are unclear. Here, the authors use a bioinformatics approach to identify the role of IGF1 in human embryo development, and from this, propose a culture medium with IGF1 together with Activin to sustain hESCs in the absence of FGF.